Pendampingan Digital Marketing UMKM untuk Tingkatkan Daya Saing Desa Kelaten - Novita Sari; Firmansyah Yunialfi; Hendrawan Harahap; Omega Septiani Gultom; Inka Fernanda Putri; Hafizh Zulfa; Wahyu Miran Antomi; Triaden Ade Putra (Penerbit Goodwood, 2026)
Purpose: This program aims to assist and socialize digital marketing for MSMEs in Kelaten Village to improve their competitiveness in the digital economy era by enhancing knowledge, skills, and market reach through online platforms. Research Methodology: The program was implemented through socialization, training, and mentoring activities for MSMEs in Kelaten Village. It involved interactive workshops, practical demonstrations of digital marketing tools, and hands-on guidance in creating social media content and promoting products online. A participatory approach ensured active participant involvement. Results: The program significantly improved the digital literacy and marketing skills of MSMEs. Participants gained practical knowledge in using social media, e-commerce platforms, and digital promotional tools, enabling them to expand market reach, increase product visibility, and apply digital marketing strategies more confidently to support business growth. Conclusions: The community service program shows that digital marketing assistance can effectively empower MSMEs in Kelaten Village. By adopting digital tools, MSMEs are better prepared to compete, enhance sustainability, and support local economic development. Limitations: The program was constrained by its short duration, varying levels of digital literacy, limited internet connectivity, and restricted access to digital devices. Contributions: This program strengthens the digital capacity of MSMEs in Kelaten Village by providing practical digital marketing skills. It also offers a community-based empowerment model that can be replicated in other rural areas to support local economic development in the digital era.